Desa Siaga Banjir Berbasis Masyarakat Sebagai Upaya Dalam Mitigasi Bencana di Kecamatan Rawas Ulu Kabupaten Musirawas Utara - Purwani, Fenny; Nopriani, Fathiyah; Yudiani, Ema (LPPM STIKOM Tunas Bangsa, 2025)
The low level of community preparedness in facing disasters, especially floods, is often exacerbated by the lack of digital literacy in the community in utilizing information technology. This study aims to examine the level of digital literacy and community preparedness in Rawas Ulu District in facing flood disasters and to review whether there is a correlation between the ability to utilize information technology and increasing such preparedness. A qualitative approach was used in this study to analyze knowledge and use of information technology, obstacles faced in its use, and community understanding of flood mitigation. Data were obtained from two types of instruments, namely 1) Knowledge and use of information technology with 6 (six) variables; 2) Community knowledge related to flood disaster mitigation with 5 variables. The results of the study showed that the majority of respondents understood the risk of flooding 88%, but there were still limitations in knowledge of disaster mitigation. The use of information technology, especially social media, was quite high at above 90%, but digital literacy was still low. Another interesting finding was that there was a positive correlation of 70% between the ability to use information technology and community awareness of flood mitigation in Rawas Ulu District. The results of this study highlight the need to increase the potential use of information technology in improving community preparedness in flood mitigation and recommend the development of community-based mitigation programs by forming information communities.